1985
DOI: 10.1111/j.1464-410x.1985.tb08984.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical Localisation of Prostate‐specific Antigen: Specificity and Application to Clinical Practice

Abstract: An immunocytochemical method to localise prostate-specific antigen (PSA) in paraffin sections was used to establish the prostatic origin of both primary and metastatic tumours. The specificity of the technique was confirmed in 65 known primary (63 PSA-positive) and 17 metastatic prostatic carcinomas (16 PSA-positive). Thirteen non-prostatic primary carcinomas and a series of benign proliferative and malignant conditions which might be considered in the morphological differential diagnosis of prostatic adenocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(13 citation statements)
references
References 12 publications
0
12
1
Order By: Relevance
“…In our experience, PSA is very sensitive and labels 95% of poorly differentiated prostatic adenocarcinomas. Moreover, in our study, PSA is more sensitive than PSAP, although some studies have shown opposite results [30,31]. The staining pattern for PSA and PSAP is cytoplasmic and granular with sometimes luminal accentuation.…”
Section: Distinction Of High-grade Invasive Prostatic Adenocarcinoma contrasting
confidence: 41%
“…In our experience, PSA is very sensitive and labels 95% of poorly differentiated prostatic adenocarcinomas. Moreover, in our study, PSA is more sensitive than PSAP, although some studies have shown opposite results [30,31]. The staining pattern for PSA and PSAP is cytoplasmic and granular with sometimes luminal accentuation.…”
Section: Distinction Of High-grade Invasive Prostatic Adenocarcinoma contrasting
confidence: 41%
“…These results demonstrate that a known biomarker protein such as PSA can be sensitively quantified in needle-biopsy samples of cancer tissue. However, it is known that serum PSA levels do not always predict the presence of prostate cancers (Ford et al, 1985;Coombs et al, 1998;Gupta et al, 2004). It is anticipated that proteomic techniques can provide the identification of additional protein biomarkers that may be used in conjunction with PSA to increase the specificity and sensitivity in prostate cancer detection.…”
Section: Development Of Dtp Technologymentioning
confidence: 99%
“…3,4 Most PaC cases show immunoreactivity for PSA and PAP, but this reactivity varies considerably with tumour grade and post-therapy status. 7,8 In well-differentiated PaC, the positivity for both markers is 100%. However, in poorly differentiated PaC, PSA positivity drops to 85% and PAP to 95%.…”
Section: Introductionmentioning
confidence: 99%
“…However, in poorly differentiated PaC, PSA positivity drops to 85% and PAP to 95%. [7][8][9] Nevertheless, some authors have reported that expression of these two markers might be lacking in 5% of high-grade PaC and in metastatic disease. 8 Others have shown that they might be reduced in expression in some treated cases.…”
Section: Introductionmentioning
confidence: 99%